2011
DOI: 10.1007/s00403-011-1181-5
|View full text |Cite
|
Sign up to set email alerts
|

A simple, noninvasive and efficient method for transdermal delivery of siRNA

Abstract: Effective delivery of therapeutic agents is the most challenging hurdle in the use of RNA interference for research and in the clinic. Here, we assessed whether a short synthetic peptide, ACSSSPSKHCG (TD-1), could be transported through rat footpad (follicle-free) skin and efficiently deliver small interfering RNA (siRNA) to knock down a target gene. Fluorescence microscopy revealed that topical co-administration of FITC-labeled TD-1 and FAM-labeled siRNA distributed uniformly from the epidermis to the subcuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…SNA constructs are able to penetrate the stratum corneum of intact skin, rapidly enter epidermal and dermal cells, and knock down epidermal targets (17). In contrast to SNAs, other topical siRNAbased therapies require epidermal disruption by physical [e.g., injection, tape stripping (23), laser, or ultrasound] or chemical (e.g., conjugation to peptides or lipoplexes or incorporation into other types of nanoparticle structures, lentiviruses, or gels) means for RNAi penetration through the epidermal barrier and into KCs (24)(25)(26)(27)(28)(29)(30)(31). siRNA SNAs are unique, highly anionic constructs that do not require additional chemical modifications to facilitate transportation through the stratum corneum or entry into cells.…”
Section: Discussionmentioning
confidence: 99%
“…SNA constructs are able to penetrate the stratum corneum of intact skin, rapidly enter epidermal and dermal cells, and knock down epidermal targets (17). In contrast to SNAs, other topical siRNAbased therapies require epidermal disruption by physical [e.g., injection, tape stripping (23), laser, or ultrasound] or chemical (e.g., conjugation to peptides or lipoplexes or incorporation into other types of nanoparticle structures, lentiviruses, or gels) means for RNAi penetration through the epidermal barrier and into KCs (24)(25)(26)(27)(28)(29)(30)(31). siRNA SNAs are unique, highly anionic constructs that do not require additional chemical modifications to facilitate transportation through the stratum corneum or entry into cells.…”
Section: Discussionmentioning
confidence: 99%
“…[172173] TD-1 could enhance the transdermal delivery of insulin when co-administered topically, lowering the serum glucose level in rats. TD-1 peptide has also been used to increase the transdermal delivery of other macromolecules such as hGH, [172, 174] siRNA, [175] botulinum neurotoxin type A (BoNT-A), [176] and CsA. [177] The mechanism by which TD-1 penetrates the SC is unclear.…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%
“…[177] The mechanism by which TD-1 penetrates the SC is unclear. [175] TD-1 has been shown to also disrupt tight junctions (see Section 3.1) by interacting with the Na + /K + -ATPase beta-subunit (ATP1B1) on keratinocytes. [178] TD-1 can also enable the transdermal delivery of macromolecular drugs such as insulin through hair follicles.…”
Section: Transdermal Drug Deliverymentioning
confidence: 99%
“…The first of these peptides discovered using phage-display screening was TD-1 (ACSSSPSKHCG) [42]. Lin et al showed TD-1 could enhance transport of GAPDH siRNA into viable tissue in the skin, as well as subcutaneous tissue, and silence GAPDH expression [43]. Co-incubation of GAPDH siRNA with TD-1 resulted in similar GAPDH expression levels as intradermal injection, while expression levels for both methods of application were significantly less than siRNA applied on the skin without peptide [43].…”
Section: Methods Of Transport Enhancementmentioning
confidence: 99%